ERGONOMICS AND OCCUPATIONAL PHYSIOLOGY: A MULTIPROFESSIONAL APPROACH TO WORK - Nunes, Antônio José Ribeiro (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2022)
In ergonomics, approaches, perspectives and purposes in relation to work are presented from a multiprofessional nature, insofar as it covers disciplines that bring contributions to ergonomics in its application in the reality of work, with improvement of operating conditions, relocation, reform and application of ergonomic projects. The research problem presents the following question: What are the multidisciplinary approaches used in the context of ergonomics in companies to reduce physiological and biomechanical damage in the work environment? The objective of this article is to identify in ergonomics and occupational physiology the approaches, perspectives and purposes in relation to the work of a multiprofessional nature. It was intended to demonstrate the concept of ergonomics in work relationships; indicate the interdisciplinary and multiprofessional nature of ergonomics; to point out the biomechanical and physiological aspects in the context of organizational ergonomics. The assumptions of the study indicate that the application of ergonomics and its approaches is necessary in organizations in the creation of projects in technologicalenvironments where repetitive activities generate occupational diseases, requiring prevention mechanisms through the creation of ergonomic projects aimed at the nature of work in situations that require corrective action. From the use of methods and steps, ergonomics allows a new perception of the functioning of a company, from the understanding of the work carried out to conceive the work situations in which workers have control over physical, mental and psychic balance and for an improvement of the system. In order to respond to the objectives of the study and the problem pointed out, it was decided to carry out a bibliographic research based on the theoretical foundations of the authors. The results showed that ergonomics deals with the transformation of the work environment for the biomechanical and physiological adaptation to the type of work activity. Therefore, it must be part of the company's culture, favoring transformations from the insertion of ergonomic projects to the optimization of human work, quality and productivity in a safe and healthy environment. Regarding the biomechanical and physiological aspects of organizational ergonomics, there is a need to evaluate the postural dynamics of the human body and its direct relationship with the workload and efficient adaptation to avoid diseases.